Indigenous knowledges and perspectives in university journalism education: Exploring experiences, challenges and opportunities. Issue 1 (1st June 2022) - Thomson, T. J.; McLaughlin, Julie; King-Smith, Leah; Bell, Aaron; Tsimpikas, Matt
News media coverage of Indigenous Australian peoples and perspectives is often absent or, when present, unfair or shallow in context or understanding. This raises the question of how much ‐ and what kind of ‐ exposure to Indigenous knowledges and perspectives journalists-in-training receive in their university studies. To find out, this study analyses 30 unit outlines and assessment details of journalism subjects at three Australian universities. It follows this analysis with interviews of seventeen undergraduate journalism students at these universities to explore their perceptions of if and how their journalism programmes paid attention to Aboriginal and Torres Strait Islander topics and perspectives in the classroom setting. The results reveal that the journalism students in this sample, even those from the same university, had an uneven experience related to Indigenous knowledges and perspectives in their university journalism subjects. This testifies to the generic nature of unit outlines and learning objectives and to the broad discretionary power that individual tutors and lecturers have to shape the flow of information that is engaged with during the learning opportunities they oversee. Student recommendations for how Indigenous knowledges and perspectives could be more usefully integrated into journalism education were also gathered and reported.